Propranolol inibe a invasão da célula hospedeira por formas metacíclicas do Trypanosoma cruzi - Fresqui, Silene de Freitas Macedo [UNIFESP] (2016)
The invasion of the host cell is a crucial step for the establishment of Trypanosoma cruzi infection, the protozoan parasite that causes Chagas disease. The mechanisms involved in the entry of T. cruzi in to the cells are only partially known. The available information indicates that the interaction of metacyclic trypomastigotes, form of the parasite found in the insect vector and responsible for initiating infection in the mammalian host, target cells through gp82, a surface molecule of the parasite. It triggers signaling cascades in the host cells resulting in mobilization and exocytosis of lysosomes, an event that requires the participation of microtubules.It is known that host cell surface components are involved in this process. During experiments in which different ligands of cell receptors were tested, we observed that pretreatment with propranolol, an antagonist of ?-adrenergic receptor, is able to significantly inhibit the entry of metacyclic forms (CL strain) in HeLa cells, whereas isoproterenol, an ?-adrenergic receptor agonist, showed no effect. The inhibitory activity of propranolol was detected at 10 µM, and was even higher at 50 µM. We observed that propranolol acts predominantly on the host cell, as preincubation of cells for 30 minutes with propranolol led to a reduction in the levels of internalized parasites. The same effect was not seen pre-treating the parasites before invasion. To determine whether propranolol affected the mobilization of lysosomes induced by gp 82 and required for invasion, HeLa cells were treated for 30 minutes with 10 µM of the drug, washed, and incubated in PBS++ a nutritionally depleted medium that induces lysosomal exocytosis. Immunofluorescence analysis showed that this pretreatment interfered with the mobilization of lysosomes, causing retention of these organelles in the perinuclear region. Similarly, propranolol blocked the lysosome mobilization caused by gp82. These results indicate that propranolol interferes with cell signaling promoted by gp82 when inducing exocytosis of lysosomes, a process required for cellular invasion of metacyclic forms.